Consumers, Designers and Managers: application of means-end chain model for fashion-clothing product development (ModaPalavra e-periódico, 2016)
The main aim of this study is to find a methodological tool able to support product development decision-making teams. The approach considers three main stakeholders: consumers, designers and companies. Qualitative and quantitative analyses were carried out based on primary data gathered in the UK, Brazil and China. The Gutman’s Means-End Chain Model (1982), comprised of Attributes, Consequences and Values, was used for the analyses. The results demonstrate that designers and companies are far from achieving synergy with consumers. The Means-End Model blending stakeholder interests seems to be an effective tool to support the decision-making process in fashion-clothing design.
Keywords: design management; research methods; garment